CHARACTER RECOGNITION USING DEEP LEARNING ALGORITHM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper describes deep learning algorithms for character recognition. Thehuge amount of data and algorithms now makes it easier to train detailed neuralnetworks. Character recognition is another application running using otherapproaches.This paper provides a CNN (Convolutional Neural Network) -based characterrecognition method. Trainyour dataset and classify it to see the results.A characterrecognition system was designed using image segmentation. Character recognition isdone by the help of the python programminglanguage